Aug um Aug. - Ronte, Dieter; Weiermair, Peter (Wien : Galerie Krinzinger, 1986)
Anzinger, Siegfried ; Attersee, Christian Ludwig ; Bohatsch, Erwin ; Brus, Günter ; Cibulka, Heinz ; Gironcoli, Bruno ; Kaletsch, Clemens ; Kogler, Peter ; Kowanz, Brigitte ; Lassnig, Maria ; Mosbacher, Alois ; Nitsch, Hermann ; Oberhuber, Oswald ; Pichler, Walter ; Rainer, Arnulf ; Schmalix, Hubert ; Schwarzkogler, Rudolf ; Trawöger, Ernst ; Trenkwalder, Elmar ; Walde, Martin ; Weiler, Max ; Weinberger, Lois ; Wurm, Erwin
Aug um Aug, Galerie Krinzinger, Wien, anlässlich der Eröffnung der Galerie Krinzinger, Wien, am 24. Mai 1986
Duits
kunstcatalogus